a.
(( x-5) × 2 + 14) :2 + 1 =21
(( x-5) × 2 + 14) :2 = 21 - 1
(( x-5) × 2 + 14) = 20 × 2
2x - 10 + 14 = 40⇒2x = 40 - 4⇒ 2x = 36
⇒ x = 18
b)
(((x+3):4)+8) × 5 - 12 =38
(((x+3):4)+8) × 5 = 38 + 12
(((x+3):4)+8) = 50 : 5
(((x+3):4)+8) = 10
(x + 3 ) + 8 × 4 = 10 × 4
x + 3 = 40 - 32⇒ x + 3 = 8 ⇒ x = 8 - 3
⇒ x = 5
c.
20 : ((3 × (x-6) + 20) : 8) + 5 = 10
20 : ((3 × (x-6) + 20) : 8) = 10 - 5
c. 20 : ((3 × (x-6) + 20) : 8) = 5
20 × 8 = 5 × (3 × (x-6) + 20)
160 = 5 ( 3x - 18 +20)⇒160 = 15x +10⇒150 = 15x⇒ x =150 :15
x = 10
d.
10 - ( 29 + ((3 x + 4) - 5) :5 - 8) : 11 =8
10 - 8 = ( 29 + ((3 x + 4) - 5) :5 - 8) : 11
2 = (29 + (3x -1) / 5 - 8) : 11
2 = [29 + (3x -1-40)/5]:11
2=(104 + 3x)/5 × 1/11⇒2 × 5 × 11 = 104 + 3x⇒110 - 104 = 3x
6 = 3x ⇒ x = 6 : 3
⇒ x = 2